Accountability when hierarchical authority is absent: views from public-private partnership practitioners - Acar, Muhittin; Yang, Kaifeng; Guo, Chao (2008)
What function does accountability serve in public-private partnerships where one partner has no authority over others and no control over results? This article aims to shed light on this question by studying participants of partnerships formed between K-12 public schools and private and/or nonprofit organizations. Findings support the notion that accountability plays a greater role in public management than indicated by the idea of answerability. Five potential functions of accountability are identified: mapping and manifesting expectations, mobilizing and motivating (ex-ante), monitoring and measuring progress and performance, modifying, and mobilizing and motivating (ex-post). - Reproduced.
Keywords: Accountability; Public private partnership